Long-Lasting Negative Effects of Learning Tasks During Early Life in the Three-Spined Stickleback - Álvarez-Quintero, Náyade; Velando, Alberto; Kim, Sin-Yeon (Frontiers in Ecology and Evolution, 2020)
Early environment often has profound effects on phenotypic development that last throughout the lifetime. It has been suggested that unpredictable environments may favour cognitive abilities. However, cognitive challenges during development may result in life-history trade-offs, because complex neural reorganization required for coping with these challenges entails stress and energy costs. In this study, we experimentally tested whether early exposure to different cognitive challenges influences cognitive ability, brain size and life-history traits in the three-spined stickleback (Gasterosteus aculeatus). For this, juvenile sticklebacks were challenged over a two-month period to resolve four different learning tasks. Contrary to our predictions, individuals trained in learning tasks later showed a reduced ability to solve a new maze task, suggesting that these learning tasks during early life may impair the ability to cope with new cognitive challenges. Females from the learning task group showed smaller optic tectum volume than the control females. Fish from the learning task treatment reduced their growth during the experiment, then accelerated growth to catch up until the breeding season. Sticklebacks reared in an environment with learning tasks also suffered a greater mortality than the controls both during and after the experiment. For the first time to our knowledge, we demonstrated direct costs of living in environments with cognitive challenges by tracking long-term performances of sticklebacks exposed to dynamic challenges during early life. Our results show that environmental challenges during ontogeny trigger plastic responses, but contrary to the common belief, do not improve the ability to cope with new cognitive challenges.